Analisis Hukum Fiqh dan Hukum Positif Terhadap Nikah Beda Agama - M. Idris; Ahmad Azmi Perkasa Alam (ASIAN PUBLISHER, 2023)
This study examines interfaith marriage from the perspective of fiqh law and positive law. Marriage is the result of affection between a man and a woman, so limiting marriage to religion is one of the conflicts that often occurs, interfaith marriage is something that is difficult to separate, especially those who adhere to the teachings of pluralism in Indonesia. So from here the researcher considers it important to raise the problems that occur in interfaith marriages. In this study the researchers used normative legal research, namely what we know as library law research, namely legal articles carried out by researching based on materials sourced from libraries. Sources of data used by the author of the article in this writing include primary legal materials (binding legal materials). Data collection techniques using library research techniques. The selection of literature is carried out as carefully as possible by considering the author's authority in the field under study. This study also examines in detail the law of interfaith marriage in terms of Islamic law following the as-Syafi'i school, and also links civil law and positive law in Indonesia, as well as the MUI fatwa.